Effect of supplementation strategies and the use of exogenous xylanase enzyme on ruminal fermentation, digestibility, animal performance, and carcass characteristics of Nellore bulls grazing during dry season - Miorin, Renan L. [UNESP]; Batista, Luis H.C. [UNESP]; Nascimento, Felipe A. [UNESP]; Silva, Luiz F. Costa e; Koontz, Anne; Pettigrew, James E.; Resende, Flávio D. [UNESP]; Siqueira, Gustavo R. [UNESP] (Elsevier, 2022)
Two experiments were conducted to assess the effects of two different supplementation strategies and the use of xylanase enzyme (Enz) on ruminal fermentation, total tract digestibility, animal performance, and carcass characteristics of Nellore bulls grazing during the dry season. In the experiment 1, animal performance was evaluated in a 2-yr study, 28 Nellore bulls (442 ± 39 kg of body weight (BW); 24 ± 4 months old; yr 1) and 48 Nellore bulls (447 ± 37 kg BW; 24 ± 4 months old; yr 2) were allotted to a randomized block design in a 2 × 2 factorial arrangement. The factor 1 was supplementation strategy of a concentrated feed: constant rate (10 g/kg BW/d) or stair-step strategy (4, 8, 12, and 16 g/kg BW/d) with increases every 35 days in yr 1 and every 28 days in yr 2. The factor 2 was xylanase enzyme inclusion: with or without exogenous xylanase enzyme (Supplied at 15 mg/kg BW/d). The following parameters were measured: nutrient intake, apparent digestibility, animal performance, and carcass characteristics. The experiment 2 was conducted only in year 1, the same treatments of the experiment 1 were applied to assess the pH and the ruminal fermentation profile using 8 Nellore bulls with ruminal cannula (622 ± 13.7 kg) in a completely randomized design. Experiment 1, no difference was observed among treatments on the total DM intake, apparent digestibility of DM, OM, NDF and CP, and animal performance based on live weight (ADG, feed efficiency of supplement intake, and final BW). Animals receiving the stair-step supplementation strategy had higher (P < 0.01) proportion of forage in their diet and the daily supplement intake was slightly lower (P = 0.01) than the constant supplementation. The supplementation strategy factor did not affect carcass ADG, final HCW, nor carcass adjusted final BW, while the use of enzyme increase (P < 0.01) carcass ADG, adjusted final body weight, and carcass dressing percentage and there is a tendency for greater final hot carcass weight (P = 0.08). Experiment 2, the average ruminal pH was higher in the animals receiving Enz in the stair-step supplementation, and lower in cattle on the same supplementation strategy without Enz (P < 0.01). The use of Enz generate lower total quantification of ruminal VFA and increased the acetate: propionate ratio (P = 0.02). In summary, the stair-step supplementation strategy did not present any benefit to animal performance and carcass characteristics. The use of xylanase enzyme, independent of the supplementation strategy, can improve animal performance based on carcass gain.
Keywords: Carcass performance; Fibrolytic enzyme; Grain-on-grass feeding; Nutrition; Supplementation